Microcephaly measurement in adults and its association with clinical variables - Nicole Rezende da Costa; Livia Mancine; Rogerio Salvini; Juliana de Melo Teixeira; Roberta Diehl Rodriguez; Renata Elaine Paraizo Leite; Camila Nascimento; Carlos Augusto Pasqualucci; Ricardo Nitrini; Wilson Jacob-Filho; Beny Lafer; Lea Tenenholz Grinberg; et al. (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To establish a microcephaly cut-off size in adults using head circumference as an indirect measure of brain size, as well as to explore factors associated with microcephaly via data mining. METHODS In autopsy studies, head circumference was measured with an inelastic tape placed around the skull. Total brain volume was also directly measured. A linear regression was used to determine the association of head circumference with brain volume and clinical variables. Microcephaly was defined as head circumference that were two standard deviations below the mean of significant clinical variables. We further applied an association rule mining to find rules associating microcephaly with several sociodemographic and clinical variables. RESULTS In our sample of 2,508 adults, the mean head circumference was 55.3 ± 2.7cm. Head circumference was related to height, cerebral volume, and sex (p < 0.001 for all). Microcephaly was present in 4.7% of the sample (n = 119). Out of 34,355 association rules, we found significant relationships between microcephaly and a clinical dementia rating (CDR) > 0.5 with an informant questionnaire on cognitive decline in the elderly (IQCODE) ≥ 3.4 (confidence: 100% and lift: 5.6), between microcephaly and a CDR > 0.5 with age over 70 years (confidence: 42% and lift: 2.4), and microcephaly and males (confidence: 68.1% and lift: 1.3). CONCLUSION Head circumference was related to cerebral volume. Due to its low cost and easy use, head circumference can be used as a screening test for microcephaly, adjusting it for gender and height. Microcephaly was associated with dementia at old age.